Optimalisasi Manajemen Bisnis Syariah melalui Penguatan Aspek Hukum Ekonomi Syariah Perspektif Praktis dan Teoretis - Farida Yanti, Reni (STIS DAFA MATARAM, 2025)
This study analyzes strategies for optimizing Islamic business management through strengthening Islamic economic law from practical and theoretical perspectives. Using a qualitative approach with library research and semi-structured interviews with eight informants from three Islamic business institutions in Bandung, this study identifies three main weaknesses: incomplete managerial understanding of Islamic economic law principles, inadequate contract documentation, and insufficient integration of sharia supervision into daily operations. The study proposes strategies including strengthening sharia literacy, standardizing contract documentation, and integrating sharia oversight into operational management systems. The resulting conceptual framework serves as a practical guide for Islamic business institutions to enhance sharia compliance and public trust.